2013
DOI: 10.1007/978-3-642-40450-4_66
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Fault-Tolerant BFS Trees

Abstract: A fault-tolerant structure for a network is required to continue functioning following the failure of some of the network's edges or vertices. This paper considers breadth-first search (BFS) spanning trees, and addresses the problem of designing a sparse fault-tolerant BFS tree, or FT-BFS tree for short, namely, a sparse subgraph T of the given network G such that subsequent to the failure of a single edge or vertex, the surviving part T of T still contains a BFS spanning tree for (the surviving part of) G. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(95 citation statements)
references
References 34 publications
1
94
0
Order By: Relevance
“…Another common variant is faulttolerant spanners or distance preservers, which must (approximately) preserve distances even after some edges "fail." Parter and Peleg [35] obtained matching upper and lower bounds for BFS structures in the presence of one fault, and Parter [34] obtained upper and lower bounds for the two fault case. Interesting fault-tolerant spanners were constructed in [17,33,21,10,15].…”
Section: Other Related Workmentioning
confidence: 95%
“…Another common variant is faulttolerant spanners or distance preservers, which must (approximately) preserve distances even after some edges "fail." Parter and Peleg [35] obtained matching upper and lower bounds for BFS structures in the presence of one fault, and Parter [34] obtained upper and lower bounds for the two fault case. Interesting fault-tolerant spanners were constructed in [17,33,21,10,15].…”
Section: Other Related Workmentioning
confidence: 95%
“…Bilò, Gualà, Leucci, and Proietti [5] showed that any weighted undirected graph has a fault tolerant (1+ )-shortest path subgraph of size O((1/ 2 )n log n). Parter and Peleg [18] showed that any unweighted (un)directed graph has a fault tolerant exact shortest path subgraph with O(n 3/2 ) edges. They also showed a matching lower bound.…”
Section: Related Workmentioning
confidence: 99%
“…Parter and Peleg [18] showed that even in the case of unweighted undirected graphs there are graphs such that the size of their fault tolerant exact shortest path subgraph is at least Ω(n 1.5 ). Bilò, Gualà, Leucci, and Proietti [5] showed that any weighted undirected graph has a fault tolerant (1 + )-shortest path subgraph of size O((1/ 2 )n log n).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parter and Peleg [62] considered the problem of computing a subgraph that preserves shortest paths from s sources after a single edge or vertex failure. They proved that Θ(s 1/2 n 3/2 ) edges are necessary and sufficient, for every s. See also [14,17,18,23,31,61,63] for spanners (subgraphs) that preserve approximate distances subject to edge or vertex failures.…”
Section: Introductionmentioning
confidence: 99%